The Effects of Sleep Deprivation on Pain Inhibition and Spontaneous Pain in Women - Smith, Michael T.; Edwards, Robert R.; McCann, Una D.; Haythornthwaite, Jennifer A. (Sleep (New York, N.Y.), 2007)
Impaired central pain modulation is implicated in the pathophysiology of chronic pain. In this controlled experiment, we evaluated whether partial sleep loss altered endogenous pain inhibition and reports of spontaneous pain. Thirty-two healthy females were studied polysomnographically for 7 nights. On Nights 1-2 (Baseline), subjects slept undisturbed for 8 hours. After Night 2, subjects were randomized to Control (N = 12), Forced Awakening (FA, N = 10), or Restricted Sleep Opportunity (RSO, N = 10) conditions. Controls continued to sleep undisturbed. FA underwent 8 forced awakenings (one per hour) on Nights 3-5. RSO subjects were yoked to FA on total sleep time (TST), receiving partial sleep deprivation by delayed bedtime. On Night 6, both FA & RSO underwent 36 hours total sleep deprivation (TSD), followed by 11-hour recovery sleep (Night 7). Subjects completed twice-daily psychophysical assessments of mechanical pain thresholds and pain inhibition (Diffuse Noxious Inhibitory Controls), via use of a conditioning stimulus (i.e., cold pressor) paradigm. FA and RSO demonstrated 50% reductions in total sleep time and increases in nonpainful somatic symptoms during partial sleep deprivation. While sleep deprivation had no effect on pain thresholds, during partial sleep deprivation the FA group demonstrated a significant loss of pain inhibition and an increase in spontaneous pain; neither of the other 2 groups showed changes in pain inhibition or spontaneous pain during partial sleep deprivation. These data suggest that sleep continuity disturbance, but not simple sleep restriction, impairs endogenous pain-inhibitory function and increases spontaneous pain, supporting a possible pathophysiologic role of sleep disturbance in chronic pain.